High-Performance Composite Event Monitoring System Supporting Large Numbers of Queries and Sources - LEE, SangJeong (Institutional Knowledge at Singapore Management University, 2011)
This paper presents a novel data structure, called Event-centric Composable Queue (ECQ), a basic building block of a new scalable composite event monitoring (CEM) framework, SCEMon. In particular, we focus on the scalability issues when large numbers of CEM queries and event sources exist in upcoming CEM environments. To address these challenges effectively, we take an event-centric sharing approach rather than dealing with queries and sources separately. ECQ is a shared queue, which stores incoming event instances of a primitive event class. ECQs are designed to facilitate efficient shared evaluations of multiple queries over very large volumes of event streams from numerous event sources. ECQs are composable and form a single shared network within which multiple queries are simultaneously evaluated. In this paper, we present efficient shared processing techniques operating on top of the proposed shared ECQ network. The performance evaluation shows that the proposed approach achieves a high level of scalability compared to conventional separate processing approaches in large-scale CEM environments.